Pengaruh Ukuran Perusahaan, Return On Asset Dan Price Book Value Terhadap Harga Saham Pada Pt Adaro Energy Tbk Periode 2014 - 2023 - Eka Pratiwi, Yunita; Mardiati , Dijan (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
The purpose of this study was to determine the effect of Firm Size, Return on Assets (ROA), and Price Book Value (PBV) on Stock Prices at PT Adaro Energy Tbk, a company listed on the Indonesia Stock Exchange, specifically PT Adaro Energy Tbk for the period 2014–2023. This is a quantitative study using linear regression analysis. Data were processed using SPSS software version 26. The sampling technique used was purposive sampling based on specific criteria. The results of the partial test (t-test) indicate that Firm Size has a positive and significant effect on Stock Price with a calculated t-value of 4.778 > table t-value of 1.860 and significance of 0.001 < 0.05. Meanwhile, ROA has a positive and significant effect on Stock Price with a calculated t-value of 7. 085 > t-table 1.860 and significance 0.000 <0.05. Similarly, PBV also has a positive and significant effect on Stock Price with t-count 2.766 > t-table 1.860 and significance 0.024 <0.05. The simultaneous test (F-test) shows that the three independent variables together have a significant effect on Stock Price, with F-calculated 98.031 > F-table 4.35 and significance 0.000 < 0.05. The coefficient of determination (Adjusted R²) value of 0.970 indicates that 97% of the variation in Stock Price can be explained by Firm Size, ROA, and PBV. This study shows that internal factors play an important role in determining the share price of PT Adaro Energy Tbk. These results can be used as a reference for investors in making decisions based on the company's financial indicators.